Use of Elderly Donors in Liver Transplantation: A Paired-match Analysis at a Single Center. Issue 2 (August 2018) - Ghinolfi, Davide; Lai, Quirino; Pezzati, Daniele; De Simone, Paolo; Rreka, Erion; Filipponi, Franco
Abstract : Objective: To evaluate the use of elderly donors in liver transplantation (LT) and identify risk factors associated with a worse outcome. Summary Background Data: Use of livers from very old donors could expand the donor pool but is not universally implemented. Methods: This is a retrospective, single-center medical record review. From January 2001 to December 2014, 1354 LTs were performed. After exclusion of donors <18 years, ABO-incompatible LT, re-LT and UNOS 1 status patients, LT recipients were stratified into 2 groups based on donor age: 18–69 (n=692) vs. ≥70 years (n=515) then matched using a propensity score approach. Two groups were finally matched (young group = 448 cases; old group = 515 cases). Results: The median (interquartile range [IQR]) follow-up was 5.0 (2.0–8.4) years. Comparing the 2 identified groups, no differences were observed regarding early retransplants (1.8 vs. 2.9; P = 0.3), HCV-related death (7.6 vs. 8.7%; P = 0.6), vascular (5.8 vs. 5.0%; P = 0.7), and biliary complications (16.5 vs. 18.6%; P = 0.4). On multivariate analysis, independent risk factors for graft loss were: HCV-positive recipient (HR = 2.1; 95% CI = 1.6–2.7; P < 0.001), donor age (HR = 1.0; 95% CI = 1.0–1.0; P < 0.001), cold ischemia time (HR = 1.0; 95% CI = 1.0–1.0; P = 0.042), and donor history of diabetes mellitus (HR = 1.48; 95% CI = 1.03–2.13; P = 0.036). Conclusions: Use of elderly donors is not associated per se with an increased risk of vascular and biliary complications. In the presence of cold ischemia time and diabetes mellitus, appropriate donor-to-recipient matching is warranted.